Expression of Aintegumenta-like Gene Related to Embryogenic Competence in Coconut Confirmed by 454-pyrosequencing Transcriptome Analysis - Bandupriya, H. D. D. (International Coconut Community Journal, 2015)
A member of the Aintegumenta sub-family of Apetala gene family encoding two APETALA2 (AP2) domains was isolated and termed as Cocos nucifera Aintegumenta like gene (CnANT). The deduced amino acid sequence of the conserved domains shared a high similarity with Aintegumenta-Like (ANT like) genes in Arabidopsis thaliana, Elaeis guineensis, Oryza sativa. Comparison of transcriptomes in different tissues revealed that CnANT transcripts were high in mature zygotic embryo (12 months after pollination; 12ME). Quantitative RT-PCR results confirmed the higher CnANT transcript accumulation in mature zygotic embryos while transcripts were rarely detected in vegetative tissues such as leaf. The expression data and global transcriptome data were therefore consistent across the embryo maturity stage and showed that CnANT could play a role in embryogenesis.